Comparison of AIMS65 and Glasgow Blatchford scores in predicting mortality in patients with upper gastrointestinal bleeding - Ak,Rohat (2021)
SUMMARY OBJECTIVE: Several mortality prediction scores are available for patients with upper gastrointestinal bleeding who visited the emergency department; however, most of the available scores include endoscopic data. Endoscopy is difficult or impossible to access for many emergencies departments worldwide. The aim of this study was to evaluate and compare the performance of the albumin, INR, alteration in mental status, systolic blood pressure and age 65 score and the Glasgow-Blatchford score in predicting mortality in patients with upper gastrointestinal bleeding who visited the emergency department and for which endoscopic data were not required. METHODS: The data of patients with acute upper gastrointestinal bleeding who visited the emergency department during the study period were retrospectively analyzed. The data were obtained from the hospital automation system using the international classification of disease codes via computer registration. The prediction accuracy of AIMS65 and Glasgow-Blatchford score was compared using the area under the receiver operating characteristic curve method. RESULTS: There were 422 patients in total; the mean age of these patients was 68.5 while 62.6% were males. The mortality rate was 30 (7.1%). The AIMS65 score performed better with an AUC 0.706 [95%CI 0.660-0.749; p<0.001] compared with the Glasgow-Blatchford score (AUC 0.542; 95%CI 0.4693-0.576; p=0.11). CONCLUSION: In this study, it was revealed that AIMS65, which is a score that can be easily calculated only with the data in the emergency department, outperformed Glasgow-Blatchford score in predicting mortality in patients with acute upper gastrointestinal bleeding who visited the emergency department.